On Fractional Orthonormal Polynomials of a Discrete Variable. (8th July 2015) - Area, I.; Djida, J. D.; Losada, J.; Nieto, Juan J.
Abstract : A fractional analogue of classical Gram or discrete Chebyshev polynomials is introduced. Basic properties as well as their relation with the fractional analogue of Legendre polynomials are presented.